Microstrip dipole antenna for VLAN application - Jamaluddin, M. H.; A. Rahim, M. K.; Abd. Aziz, Mohd. Zainol Abidin; Asrokin, A. (IEEE, 2005)
This paper describes numerical simulation, fabrication and experimental measurement of microstrip dipole antenna at 2.4 GHz for WLAN application. In this antenna design, Agilent’s ADS software using momentum simulation is employed to analyze the entire structure. The properties of antenna such as bandwidth, radiation pattern and half power beamwidth have been investigated and compared between simulation and measurements. The cross-polar isolation of the microstrip dipole antenna is in the range of 3 to 17.32 dB. The typical half power beamwidth (HPBW) of the microstrip dipole is 60º for E plane and 75º for H plane. Performance comparison between dipole and monopole antenna is also made in term of bandwidth and Input return loss.